Review of Rafael Ziegler’s (2020). Innovation, Ethics and Our Common Futures: A Collaborative Philosophy. - Hölsgens, Rick (NOvation — Critical Studies of Innovation, 2022)
In his book “Innovation, Ethics and Our Common Futures: A Collaborative Philosophy,” Rafael Ziegler sets out to critically assess the notion of innovation as a driving force in modern-day (Western) economies. He asserts that ‘innovation as technological novelty for commercial use is driving us deeper in unsustainability’ (p. v), and embarks on a philosophical journey to scrutinize the concept of innovation and its role in modern economies. In doing so, Ziegler aims to develop a sufficientarian notion of innovation, calling to embrace a broad, collaborative understanding of innovation based on pluralistic modes of provision focusing not only on markets and increasing financial welfare, but instead on nature-respecting sufficientarian principles of enough is enough – ‘within justice of a minimum threshold and of respect for upper limits to resource use’ (p. 18).